The Effect of Music Therapy on Anxiety in Hemodialysis Patients with Kidney Failure : A case report - Hunain Suci Kamila; Arina Maliya; Puji Kristini (Universitas Muhammadiyah Surakarta, 2023)
Chronic kidney failure is a health problem as a result of damaged kidney function. Newly diagnosed patients who have to undergo long-term hemodialysis often feel worried about survival, the amount of dialysis time to the body’s reaction when undergoing hemodialysis. This can create inner conflict, frustration, guilt to severe anxiety. The purpose of this case study is to determine whether there is an effect of music therapy on anxiety in patients undergoing hemodialysis with chronic kidney failure. The research method used in this study is a case study with a total number of respondents as many as 7 patients. The results of the case study showed anxiety in patients undergoing hemodialysis at the hospital after being given music therapy from a total of 7 respondents there were 3 respondents experienced normal anxiety, 2 respondents experienced mild anxiety and 2 respondents experienced moderate anxiety. These results were obtained from the administration of an anxiety the last meeting using DASS 42. The conclusion in this study showed that there was an effect of giving music therapy to patients undergoing hemodialysis with chronic kidney failure.